The double glucagon test, a new liver function test. Issue 544 (February 1971) - Verhaegen, H.; Verhaegen-Declercq, M. L.; de Beukelaer, A.; Krug, F.
Abstract : A double glucagon test was performed in 100 patients and seventeen control subjects. Two intravenous doses of glucagon (1 mg) were administered at a 1-hr interval. Glucose was determined before the first injection and 20, 25 and 30 min after both doses, and the increases after each successive dose were added up. In normal persons, the total increase in glycaemia was higher in the second than in the first hour and reached at least 110 mg. Normal values were found in cases of obstructive jaundice, cholelithiasis and adult diabetes, and abnormal values in patients with infective hepatitis, liver congestion and cirrhosis. The double glucagon test was found to be very useful for the differential diagnosis of liver cell impairment and hepatic obstruction.